A cor de queima dos suportes de porcelanatos esmaltados - Conserva, Lisandra Rafaela dos Santos (Universidade Federal de São Carlos, 2012)
Brazil is a protagonist in the market of ceramic tiles. Porcelain stoneware is part of this supply chain with added value due to its excellent technical and aesthetic features, which higher acceptance in the market. Although the color of the holder is no longer visible after application of the porcelain stoneware enameled, it is critical to the consumer: the whiteness seems to be greater value and product quality. Reddish hues are directly related to the content of chromophores ions from raw materials, mainly present in clays and phyllites, which are the major components of the mass. Accordingly, it is essential to study conditions permitting the use of raw materials with a content of chromophores ions not so restricted. Thus, this study was divided into two stages. At first several typical porcelain stoneware masses were evaluated in differents firing temperatures. Data were organized in order to identify the main variables that affect the color of burning. In the second stage, procedures were conducted in order to evaluate the efficiency of maneuvers that can improve the tone of stoneware, enabling the use of masses with higher content in chromophores ions than usual, by simple methods and readily applicable to industry. The results obtained contributed to the identification of variables responsible for color formation and found that is possible the use of raw materials with levels of chromophore ions relatively high.
Firing colour of porcelain stoneware
Keywords: Revestimento cerâmico; Porcelanato; Teor de ferro; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA